2012
DOI: 10.1007/s10384-012-0126-7
|View full text |Cite
|
Sign up to set email alerts
|

Survey of microphthalmia in Japan

Abstract: Patients with microphthalmia often have ocular and systemic anomalies. Early assessment and preservation of vision and long-term complication management are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Epidemiological studies have suggested that cataract is often found in association with microphthalmia. 8,49 Our finding that cataract was the most frequently associated eye abnormality in the NOFCD cohort (Table 2) and can be found in relatives of patients with NOFCD is consistent with these reports. There have been previous instances of pedigrees with this pairing of eye abnormalities.…”
Section: Discussionsupporting
confidence: 89%
“…Epidemiological studies have suggested that cataract is often found in association with microphthalmia. 8,49 Our finding that cataract was the most frequently associated eye abnormality in the NOFCD cohort (Table 2) and can be found in relatives of patients with NOFCD is consistent with these reports. There have been previous instances of pedigrees with this pairing of eye abnormalities.…”
Section: Discussionsupporting
confidence: 89%
“…The incidence of glaucoma is 77% in elderly patients with relative anterior microphthalmus (cornea diameter <11 mm, axial length >20 mm) (29). Microphthalmia, which is always accompanied with microcornea, is considered a primary risk factor of angle-closure glaucoma (30). Mutations in a number of genes have been linked to ASD, microcornea and microphthalmia (31)(32)(33)(34)(35)(36), and some of these were recently reported to be responsible for primary glaucoma (37,38).…”
Section: Introductionmentioning
confidence: 99%
“…Between 60 and 80% of cases of microphthalmia are syndromic, however lower incidences were found in a Japanese population with only 31% found with systemic features [61,[67][68][69]. Syndromic involvement is expected at 2.7 times higher in bilateral cases of microphthalmia rather then unilateral cases [68]…”
Section: Estimated Frequency Of the Diseasementioning
confidence: 94%